2001
DOI: 10.1002/ppul.1058
|View full text |Cite
|
Sign up to set email alerts
|

Prospective longitudinal study of urinary eosinophil protein X in children with asthma and chronic cough

Abstract: Airway inflammation is the principal abnormality in asthma and many other respiratory diseases. Eosinophils are the cells primarily involved in this process. The aim of this study was to analyze sequential changes in urinary eosinophil protein X (EPX) a biological marker of eosinophil activation in asthmatic children and chronic coughers, and to confirm the importance of such changes in evaluating the inflammatory process once regular treatment was initiated. Eighty-eight asthmatic children (AC), 33 children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 37 publications
0
27
1
1
Order By: Relevance
“…All subjects included in our study had stable well-controlled asthma, as evidenced by a median cumulative symptom score of only 17 of a maximum of 252. Conflicting data have been published on the association between uEPX/c and pulmonary function tests [21, 23]. We found a significant negative correlation between FEV 1 and uEPX/c.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…All subjects included in our study had stable well-controlled asthma, as evidenced by a median cumulative symptom score of only 17 of a maximum of 252. Conflicting data have been published on the association between uEPX/c and pulmonary function tests [21, 23]. We found a significant negative correlation between FEV 1 and uEPX/c.…”
Section: Discussioncontrasting
confidence: 63%
“…Urine samples were not all obtained at the same time of the day. Since the start of our study, it became evident that a circadian rhythm of uEPX/c with lowest levels at 7 p.m. and highest at 7 a.m. in both asthmatic and healthy controls exists [23, 2931]. Hence, diurnal variability may have introduced scatter of uEPX, thus weakening a possible correlation.…”
Section: Discussionmentioning
confidence: 99%
“…A relation with asthma symptoms and lung function has been shown, and uEPX increases significantly during asthma exacerbations [79]. A reduction in uEPX has been reported after starting inhaled corticosteroids [10]. Therefore, it has been suggested that measuring urinary EPX may be useful for monitoring the effect of ICS in asthma [3, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Below I will discuss some of the advantages and disadvantages of measuring ECP in serum/plasma and sputum and also discuss the current evidence that ECP may be a useful addition to the diagnostic armamentarium for monitoring and characterization of disease activity in the allergic patient. I will also discuss the emerging evidence that seems to show that urine measurement of EPX/EDN may be an alternative to ECP measurements in blood as a reflection of eosinophil turnover and activity (43)(44)(45)(46)(47)(48)(49).…”
Section: Monitoring Eosinophil Activity and Turnovermentioning
confidence: 99%
“…In a search for noninvasive means to monitor eosinophil involving inflammation urine measurement of EPX/EDN has emerged as a promising candidate in particular in children (44,45,48,64). In order to minimize the influence of differences in water dilution of the urine the EPX/EDN levels have to be adjusted by the creatinine concentrations unless 24 h samplings are carried out.…”
Section: Epx/edn In Urinementioning
confidence: 99%